Transmisión de volatilidad en el Mercado Integrado Latinoamericano (MILA): Una evidencia del grado de integración - Mariana Fuentes Vélez; Alejandro Pinilla Barrera (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– This paper presents the progress in the integration of the Latin American Integrated Market (MILA by its Spanish acronym) by studying the dynamic relationship between the volatilities of the markets that conform it: Colombia, Mexico, Peru and Chile. To achieve this objective, data between 2002 and 2018 from the stock exchanges' representative indices of each MILA member was used. Due to the particular characteristics of the financial series, such as non-stationarity and dynamic variance over time, time series techniques were applied, specifically, the models of the GARCH family with a multivariate approach captures the relationship existing between markets. It was found that individually all series are integrated processes of order 1 and present ARCH effects. Even though the existence of interdependence of volatility between markets is latent and varies over time, the results of this study show that this relationship does not represent a significant increase after the conformation of the MILA. This fact suggests that, although the markets are interrelated, the interdependence is not strong and therefore each of the markets maintain independence. The integration has not been fully achieved and the advantages of this have only been partially shown in each of the stock exchanges.
Keywords: C32; G15; C58; 330; MILA; Multivariate GARCH Model; stock exchange integration; volatility transmission; Latin American Stock Markets